A citation analysis of business librarianship: Examining the Journal of Business and Finance Librarianship from 1990–2014. Issue 2 (3rd April 2017) - Siciliano, Mark
ABSTRACT: This article is a bibliometric analysis of the Journal of Business & Finance Librarianship from 1990 through 2014. Authorship patterns, citations, article content, and collaboration efforts were examined and are discussed. The subgenre of business librarianship is surveyed from a bibliometric viewpoint, and the resources that helped contribute to the growth of this discipline are highlighted. Finally, content is analyzed, emphasizing some of the aspects of business librarianship that have been written about over this 24-year period.